2000
DOI: 10.1097/00005373-200002000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the International Classification of Diseases 10th Edition???based Injury Severity Score (ICISS)

Abstract: The ICISS methodology can be extended to ICD-10 horizon as a standard injury severity measure in the place of TRISS, especially when age and Revised Trauma Score were incorporated in the model. For patients with intracranial injuries, the predictive power of ICD-10-based ICISS was relatively low because of differences in the classifying system between ICD-10 and ICD-9CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 9 publications
3
24
1
Order By: Relevance
“…These findings are in keeping with previous research: Sampalis et al demonstrated a higher mortality rate among older fallers, while both Spaniolas' and Sterling' groups showed that ground level falls in older people were associated with more severe injuries and higher mortality (1,3,7). The generally low incidence of severe injuries in our study may be because we mapped ICD&10 codes to the lowest possible relevant AIS scores, thus underestimating injury severity (12). The injury patterns in our study did not conform to those found in other studies of older trauma patients.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in keeping with previous research: Sampalis et al demonstrated a higher mortality rate among older fallers, while both Spaniolas' and Sterling' groups showed that ground level falls in older people were associated with more severe injuries and higher mortality (1,3,7). The generally low incidence of severe injuries in our study may be because we mapped ICD&10 codes to the lowest possible relevant AIS scores, thus underestimating injury severity (12). The injury patterns in our study did not conform to those found in other studies of older trauma patients.…”
Section: Discussionsupporting
confidence: 92%
“…Operative procedures are also coded. Although initially based on the International Classification of Disease 9th edition (ICD-9), ICISS has also been validated for ICD-10 codes [29]. The calculation of survival risk ratios (SRRs) is central to this method (the proportion of survivors for each ICD-9 injury code).…”
Section: The Rationale For Trauma Scoringmentioning
confidence: 99%
“…However, the sample size used in this study was very small. 15 Data available in Australia and New Zealand provided a particularly good basis for testing the ICISS method in the context of ICD-10-AM coding. Mapping of the Australian and New Zealand data from ICD-10-AM to ICD-10 also allowed assessment of the applicability of ICISS to ICD-10.…”
mentioning
confidence: 99%